Blood glucose concentration for predicting poor outcomes in patients with and without impaired glucose metabolism undergoing off-pump coronary artery bypass surgery – long-term observational study - Szychta, Wojciech; Majstrak, Franciszek; Opolski, Grzegorz; Filipiak, Krzysztof J. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction: Strict glucose control is an everyday practice in the perioperative period. Elevated glucose level has a deleterious impact on clinical results, but a therapeutic target has not been stated yet. Aim : To determine a glucose concentration range affecting long-term outcomes after coronary artery bypass surgery (CABG). Material and methods : This study is a retrospective evaluation of consecutive patients treated in a university hospital in Poland from 2004 to 2008. Patients were divided into 2 groups: an impaired glucose metabolism group (IGM) if they had 1) known DM or 2) perioperative hyperglycaemia defined as ≥ 200 mg/dl; and a non-IGM group. The end point (EP) was all-cause mortality. Results: One thousand two hundred and eleven patients were covered by the analysis. The observation time was from 01.01.2004 until 01.08.2012. Patients who had maximal glucose concentrations 324 mg/dl (EP in 44.2%) (p = 0.041). Patients with IGM had a shorter survival at the end of the study (p < 0.001). The longest survival was observed in patients whose maximal glucose level was ≤ 242 mg/dl (p < 0.001) and the minimal glucose concentration was in the range 61–110 mg/dl (p < 0.001). Conclusions : Tight glucose concentration control should be performed irrespective of a diabetes diagnosis and proper treatment introduced when necessary. Maximal glucose concentration should be kept < 242 mg/dl, while the minimum should be in the range 60–110 mg/dl.